2021
DOI: 10.1108/bfj-12-2020-1108
|View full text |Cite
|
Sign up to set email alerts
|

QUICKSERV: a service quality assessment tool for the quick-service restaurant industry

Abstract: PurposeThe purpose of this study is to empirically develop and validate a practical, consistent and specific scale to assess perceived service quality at the service encounter at quick-service restaurants (QSRs).Design/methodology/approachDevelopment and validation of the scale involved a five-stage process. Data were collected from 430 customers of a QSR belonging to an international brand located in Barcelona. Surveys were applied immediately after the service encounter, using the face-to-face method. The sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 62 publications
0
28
0
2
Order By: Relevance
“…This study confirmed that the REP-SERV scale could provide valuable and contributing research results for the measurement of restaurant service quality during an epidemic. A review of the previous literature found that the DINESERV scale provides a common criterion for service quality evaluation in the restaurant industries (Knutson et al , 1996; Wu and Mohi, 2015; Chen et al , 2015; Cheng et al , 2019; Mendocilla et al , 2021; Cheng et al , 2021). Not only that, other hospitality service quality scales (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study confirmed that the REP-SERV scale could provide valuable and contributing research results for the measurement of restaurant service quality during an epidemic. A review of the previous literature found that the DINESERV scale provides a common criterion for service quality evaluation in the restaurant industries (Knutson et al , 1996; Wu and Mohi, 2015; Chen et al , 2015; Cheng et al , 2019; Mendocilla et al , 2021; Cheng et al , 2021). Not only that, other hospitality service quality scales (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, other hospitality service quality scales (e.g. GRSERV, LORSERV, service quality scale for green lodging, QUICKSERV and service quality scale for the online food delivery industry and more) can also extract common criteria for service quality evaluation in specific hospitality industries (Knutson et al , 1996; Chen et al , 2015; Lee and Cheng, 2018; Cheng et al , 2019; Mendocilla et al , 2021; Cheng et al , 2021). Therefore, the above scales have high research value and contribute to service quality evaluation in different restaurant industries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations